Climatic Controls on the Spring Phytoplankton Growing Season in a Temperate Shelf Sea. Issue 5 (11th May 2022) - Jardine, J. E.; Palmer, M.; Mahaffey, C.; Holt, J.; Wakelin, S.; Artioli, Y.
Abstract: The Northwest European Shelf is positioned directly beneath the North Atlantic Storm Track, within which the frequency and intensity of transient storms are modulated by large‐scale climatic oscillations. In temperate shelf seas, the impact of storms on the physical environment has received considerable attention, but the effect on biogeochemistry is less studied. Here, we use output from a multidecadal (1982–2015) coupled physical‐biogeochemical model supported by observations from ocean gliders to investigate phytoplankton growth throughout the winter‐spring transition. We define two separate phytoplankton growth events: the spring bloom, defined as the exponential growth following seasonal stratification, and the prebloom, occurring before stratification, and accounting for up to 22% of the total spring growth. Our results support the paradigm that light is a first‐order control, with the spring bloom initiating up to 22 days after stratification onset should light levels be too low to trigger the bloom. The prebloom is heavily influenced by the phase of the Atlantic Multidecadal Oscillation (AMO), demonstrated by an acceleration in the rate of increase of total chlorophyll concentrations (±90% confidence limit) from 7.6 ± 2.8 mg m −2 d −1 (during a positive AMO) to 13.1 ± 4.3 mg m −2 d −1 (negative AMO), due to modulation of periods of ephemeral stratification that occur between successive storms. We propose that phytoplankton growth in prebloom events might help buffer the lag between phytoplankton supply and larval recruitment, particularly during years when the spring bloom is delayed. Plain Language Summary: In temperate shelf seas, the seasonal onset of stratification is usually considered the precursor for the spring phytoplankton bloom: an exponential growth of algae that is of key biological importance to fish stocks. Seasonal stratification, whereby the water column becomes layered with warmer water on top of colder water, is initiated by more heat going into the ocean toward spring. Increasing winds, due to passing storms, delay the onset of stratification due to increased mixing. Changes in water temperatures and atmospheric pressure across the North Atlantic change the frequency and intensity of storms across Northwest Europe and influence stratification onset. Using a model that incorporates both physics and biology, we investigated how changing storm patterns from 1982 to 2015 influenced phytoplankton variability during the winter‐spring transition. Our results show that the spring bloom is limited by light, and can occur 3 weeks after stratification should light be insufficient for growth. Furthermore, we show that short‐lived stratification events throughout the winter period provide high‐light oases for phytoplankton growth. These "preblooms, " which occur before the onset of stratification, can contribute to over one fifth of the total spring phytoplankton growth and challenges the perception that winter is a biologically unproductive season. Key Points: Large‐scale climatic oscillations directly impact winter‐spring phytoplankton growth rates in NW European shelf seas Light is confirmed as a first‐order control on spring bloom initiation, which can occur 3 weeks after the onset of seasonal stratification Up to 22% of net spring phytoplankton growth occurs before the spring bloom